Analysis Tantangan Implementasi Manajemen Resiko Teknologi Agricultur: Study Kasus & Solusi Strategis Di Bandung Barat Dan Perkebunan Pituin Coffee - Muhamad Saefuloh; Fiqi Ardi Abdurahman Masdar; Muhammad Azka Julian; Alfiana (Indo Publishing, 2025)
This research examines the challenges in implementing agricultural technology risk management at Pituin Coffee Plantation in South Bandung and Mr Udin’s farm in West Bandung. Using a qualitative case study approach, this study identifies various obstacles faced in adopting modern agricultural technologies, including technical risks, financial constraints, human resource limitations, and environmental uncertainties. Primary data was collected through in-depth interviews with farm managers, field workers, and agricultural experts, complemented by field observations and document analysis. The findings reveal that the main challenges include lack of technical expertise, limited access to funding, inadequate infrastructure, and resistance to technological change among traditional farmers. This research proposes strategic solutions encompassing capacity building programs, establishment of cooperative financing schemes, development of appropriate technology infrastructure, and implementation of comprehensive risk mitigation strategies. The study contributes to understanding agricultural technology risk management in the context of Indonesian coffee plantations and provides practical recommendations for sustainable agricultural development. The results demonstrate that integrated risk management approaches combining technical, social, and economic dimensions are essential for successful agricultural technology implementation in developing regions.